Shear Wave Elastographic Characterization of Normal and Torn Achilles Tendons: A Pilot Study. (1st March 2013) - Chen, Xiang-Mei; Cui, Li-Gang; He, Ping; Shen, Wei-Wei; Qian, Ya-Jun; Wang, Jin-Rui
Abstract : Objectives: The purpose of this study was to investigate the feasibility of using quantitative shear wave elastography for assessing the functional integrity of the Achilles tendon and to summarize the changes in elasticity of ruptured Achilles tendons in comparison with normal controls. Methods: Thirty‐six normal and 14 ruptured Achilles tendons were examined with shear wave elastography coupled with a linear array transducer (4–15 MHz). The elasticity value of each Achilles tendon in a longitudinal view was measured. Results: The mean elasticity value ± SD for the normal Achilles tendons was 291.91 ± 4.38 kPa (note that there are saturated measurement phenomena for the normal Achilles tendon, so the actual value will be >300 kPa), whereas the ruptured Achilles tendons had an elasticity value of 56.48 ± 68.59 kPa. A statistically significant difference was found in relation to the findings in healthy volunteers ( P = .006). Conclusions: Our results suggest that shear wave elastography is a valuable tool that can provide complementary biomechanical information for evaluating the function of the Achilles tendon.